The Nearshore Heat Budget: Effects of Stratification and Surfzone Dynamics. Issue 11 (24th November 2019) - Sinnett, Gregory; Feddersen, Falk
Abstract: Temperature variability in the nearshore (from ≈6‐m depth to the shoreline) is influenced by many processes including wave breaking and internal waves. A nearshore heat budget resolving these processes has not been considered. A 7‐month experiment at the Scripps Institution of Oceanography Pier (shoreline to 6‐m depth) measured temperature and surface and cross‐shore heat fluxes to examine a nearshore heat budget with fine cross‐shore spatial (≈20 m) and temporal (5 day to 4 h) resolution. Winds, waves, air and water temperature, and in particular, pier end stratification varied considerably from late Fall to late Spring. The largest heat flux terms were shortwave solar radiation and baroclinic advective heat flux both varying on tidal time scales. The net heat flux is coherent and in phase with the nearshore heat content change at diurnal and semidiurnal frequencies. The binned mean heat budget has squared correlation R 2 =0.97 and best‐fit slope of 0.76. Including an elevated breaking wave albedo parameterization reduced the residual heat flux and improved the best‐fit slope. Baroclinic and barotropic advective heat fluxes have significant noise, and removing them from the heat budget improves the best‐fit slope when stratification is weak. However, when daily mean stratification is large, baroclinic advective heat flux dominates variability and is required to capture large (≈3 °C h −1 ) internal wave events. At times, large heat budget residuals highlight neglected heat budget terms, pointing to surfzone alongshore advection of temperature anomalies. Key Points: A high resolution nearshore (shoreline to 6‐m depth) heat budget, including the surfzone, closes at subtidal and tidal time scales Baroclinic advective and solar heat fluxes are the strongest terms and their relative contributions depend on mean stratification Residual in the heat budget is partially due to neglected alongshore advection of temperature anomalies